Swallow Droppings for The Chemical Properties of Alluvial Soil As Growing Medium For Ebony (Diospyros Celebica) - Abdul Rahman; Anthon Monde; Danang Widjajanto; Moh. Adnan Khaliq; Adrianton; Trisni Oktavina (Postgraduate, University of Mataram, 2024)
This study aimed to determine the effects of swallow bird droppings bokashi on several soil chemical properties such as pH, C-Organic, N, P, K, CEC, and to determine the appropriate dosage of bokashi fertilizer for the growth of ebony seedlings. This research was conducted at Permanent Nursery located at Tadulako University. This study was conducted using a completely randomized design with 5 treatments and 4 replications, 20 experimental units as: P0 (control), P1 (7 tons/ha), P2 (14 tons/ha), P3 (21 tons/ha), and P4 (28 tons/ha). The results showed that the swallow droppings bokashi fertilizer was able to improve: soil pH 7.18 to 7.55 with a neutral status, P from 41.34 to 65.06 with very high status, K from 46.26 to 53.87 with high status, C-Organic from 5.30 to 10.25 with high to very high status, and N-Total from 0.12 to 0.34 although in low status in the soil. The application of swallow droppings bokashi into the soil was very much needed. C-Organic content in swallow droppings bokashi was 50.23%, N (4.26). The application of swallow droppings bokashi with a treatment of 21 tons/ha (61.25 g/pot) was the best dose for the growth (height) and the increase number of leaves of ebony seedlings.